RETRACTED: Fundamentals and prospects of green economy in the context of ESG - Alimova Dilshoda; Khudayarov Bakhtiyar; Ruzmetov Kudrat; Turaev Fozilzhon; Safarbayeva Nigora; Bozorova Orzugul; Sa’dullayeva Maftuna; Nazarov Xasanbek (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001